Oral test washback efect and the improvement of speaking skills : - Thạch, Som (Can Tho University, 2009)
The study investigated students' motivation in learning speaking skills, students' improvement in speaking performance when oral test was obligatorily used in assessment, and the correlation between the motivation in learning speaking skills and oral performance in terms of oral test washback.